Pengaruh Kepercayaan, Kemudahan, Brand Image Dan Kualitas Informasi Terhadap Keputusan Pembelian Pada Pengguna E-Commerce Shopee (Studi Kasus pada Pengguna Aplikasi Shopee di Kota Sukoharjo) - Ana Dewi Marsalin; Christiawan Hendratmoko (Pusat Riset dan Inovasi Nasional, 2023)
This study seeks to ascertain how Shopee's online purchase choice is influenced by trust, convenience, brand image, and quality of information. The research results were evaluated using a quantitative research methodology based on respondents' responses on a Likert scale. The population of this study is every resident of Sukoharjo City, the number of samples is 100 respondents, and the Cochran formula and purposeful sampling are used to select the sample. Instrument Test, Classical Assumption Test, and Multiple Regression Test are used as data analysis techniques in this study. Secondary data is collected from online sources, old research publications, and books that show consumer choices. The findings show that Trust, Convenience, Brand Image and Information Quality all have a large impact on purchasing decisions together (F test). Trust, Convenience, Brand Image, and Information Quality all have a significant effect on purchasing decisions, at least partially (t test). Trust, convenience, brand image, and information quality influence purchasing decisions by 64.3% and 35.7%, respectively, according to the results of data processing showing that the coefficient of determination (Adjusted R Square) is 0.643. This means that other variables not seen in this study determine 35.7% of the variance of the results